PENINGKATAN KONSENTRASI BELAJAR MENGGUNAKAN METODE PEMBELAJARAN KUIS TIM PASERTA DIDIK KELAS IV SEKOLAH DASAR - Sutanto, Anita Rahmawati; Utami, Annisa Rahmayati; Hashol Haq, Muhammad Hash; Abduh, Muhammad; Lestari, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the team quiz method on improving the concentration of IVC class students at SDIT Nur Hidayah Surakarta during the learning process. The research method used in this study is classroom action research (PTK) with a Mix Methods approach that uses qualitative and quantitative analysis. This research consists of two cycles until the achievement of success indicators, in each cycle there are planning, implementation, observation, and reflection activities. The subject of this research is students of class IVC SDIT Nur Hidayah Surakarta and the object of this research is concentration of students' learning during learning. Data collection techniques using interviews, observations and questionnaires. Qualitative data will be processed using descriptive analysis with the stages of data reduction, data presentation, and conclusion drawing. Quantitative data of the research results are processed descriptively, namely calculating the percentage of the number of students who concentrate and the average score. Based on the results of the analysis, it can be seen that the application of the team quiz method in learning can effectively improve the concentration of students in class IVC SDIT Nur Hidayah Surakarta.